44.9k views
0 votes
Answer this please I need a real answer

Answer this please I need a real answer-example-1
User Drcocoa
by
4.8k points

1 Answer

1 vote

Answer:

see explanation

Explanation:

(a)

x² + 2x + 1 = 2x² - 2 ( subtract x² + 2x + 1 from both sides

0 = x² - 2x - 3 ← in standard form

0 = (x - 3)(x + 1) ← in factored form

Equate each factor to zero and solve for x

x + 1 = 0 ⇒ x = - 1

x - 3 = 0 ⇒ x = 3

-----------------------------------

(b)


(x+2)/(3) -
(2)/(15) =
(x-2)/(5) ( multiply through by 15 to clear the fractions )

5(x + 2) - 2 = 3(x - 2) ← distribute parenthesis on both sides

5x + 10 - 2 = 3x - 6

5x + 8 = 3x - 6 ( subtract 3x from both sides )

2x + 8 = - 6 ( subtract 8 from both sides )

2x = - 14 ( divide both sides by 2 )

x = - 7

--------------------------------------------

(c) Assuming lg means log then using the rules of logarithms

log
x^(n) ⇔ nlogx

log x = log y ⇒ x = y

Given

log(2x + 3) = 2logx

log(2x + 3) = log x² , so

x² = 2x + 3 ( subtract 2x + 3 from both sides )

x² - 2x - 3 = 0

(x - 3)(x + 1) = 0

x = 3 , x = - 1

x > 0 then x = 3

User Teodozjan
by
4.8k points